Impact of pterygium morphological profiles on dry eye parameters - Dong Hee Ha; Kyoung Woo Kim (Scientific Reports)
Abstract This study aims to determine whether morphological features of pterygium are linked to clinical parameters of dry eye disease. We examined 122 eyes from 109 patients with primary nasal pterygium who underwent preoperative anterior segment swept-source optical coherence tomography (AS SS-OCT, Anterion®, Heidelberg Engineering, Germany) and evaluated dry eye parameters, including the clinical severities of meibomian gland dysfunction, tear osmolarity, Schirmer I, tear matrix metalloproteinase-9 expression, and ocular surface staining. Morphological profiles of pterygium based on AS SS-OCT included horizontal invasion length (HIL), pterygium height, pterygium thickness, and the ratio of residual corneal thickness (RCT) to central corneal thickness (CCT). AS SS-OCT-guided values of anterior corneal astigmatism (ACA) and root mean square (RMS) values of lower-order aberrations (LoA) and higher-order aberrations (HoA) were also obtained. HIL was negatively correlated with corneal erosions and the Sjögren’s International Collaborative Clinical Alliance ocular staining score (SICCA OSS). Pterygium height and thickness were positively correlated with tear osmolarity, Schirmer I, and SICCA OSS. Additionally, ACA, corneal RMS LoA and HoA were negatively correlated with corneal erosions and SICCA OSS. Given that HIL inversely correlated with pterygium height and thickness, early pterygium appears to induce desiccation, pterygium surface erosions, and increased reflex lacrimation.